Solar Lighting - Pode, Ramchandra; Diouf,Boucar (New York : Springer, 2011)
Annotation Analyzing energy-efficient lighting using solar-powered LED systems, this book focuses on the interplay of energy transformation and device efficiency. Covering many aspects of renewable energy, it explains how more efficient appliances can reduce the cost of energy.
Scholarly & Professional